The inhibitory influence of rice husk ash on the alkali leaching and efflorescence extents of alkali activated granulated blast furnace slag - Nseke, Joseph; Kirkelund, Gunvor Marie; Sithole, Thandiwe (Frontiers in Built Environment, 2024)
This study investigates the inhibitory effect of rice husk ash (RHA) on the efflorescence and leaching of alkali-activated granulated blast furnace slag (GBFS). RHA consists of about 90% of microporous amorphous silica and possesses similar pozzolanic characteristics to silica fume and nano-SiO2. The specific surface area of RHA varies between 20 and 200 m2/g. RHA-GBFS-based specimens were mainly characterised through Fourier transform infrared spectroscopic (FTIR), X-ray diffraction spectrometry (XRD), thermal analyses, as well as scanning electron microscope (SEM) and energy dispersive spectrometric (EDS) analyses. Results showed that efflorescence decreases with the rise in RHA content due to the increase in the degree of reaction. The optimal RHA content was 15%. Specimen consisting of 15% RHA and 85% GBFS yielded the lowest extent of total alkali leaching, equivalent to 9.41%, while sample consisting of 100% GBFS yielded the highest degree of alkali leaching, equivalent to 29.9%. EDS analysis of 15% of specimens before and after leaching indicates a smaller decrease in Na+ ions from 27.83% to 25.25% by weight. However, the addition of RHA does not permanently inhibit alkali leaching but retard the extent of alkali leaching over time. With the increase of up to 15% RHA, CO3− peaks are nearly suppressed based on FTIR analysis, indicating that the increase in RHA mitigates the effect of efflorescence. XRD of specimens containing 10% and 15% RHA \ indicate the possible formation of hydrosodalite and sodium-calcium aluminium hydrate gel, which control the mobility of Na + ions; consequently, Na + ions are less prone to reach out.